Photocatalytic Decomposition of Formaldehyde by Combination of Ozone and AC Network with UV365nm, UV254nm and UV254+185nm. (2015) - Wang, M.Y.; Lu, Y.W.; Wu, F.; Zhang, X.J.; Yang, C.X.
Abstract: Formaldehyde (HCHO) is one of the most common indoor pollutants. Long time exposure to the environment with HCHO concentration above 0.1 mg/m 3 can cause harm to human body. In order to remove HCHO efficiently, The TiO2 /AC network film was prepared by loading nanometer particle TiO2 on the surface of activated carbon. The photocatalytic degradation of gaseous HCHO was performed by TiO2 /AC network film under the irradiation of UV365nm, UV254nm and UV254+185nm, respectively. The results show that the adsorption of AC network and byproduct ozone (O3 ) oxidation simultaneously can promote the degradation of the HCHO; under the illumination of UV254+185nm, HCHO can be degraded more effectively. The produced ozone can also be degraded below 0.214 mg/m 3 that are required by Chinese indoor air quality standard.